Applied Rasch Measurement: A Book of Exemplars Papers in Honour of John P. Keeves - Maclean, Rupert; Watanabe, Ryo.; Baker, Robyn; Boediono; Cheng, Yin Cheong; Duncan, Wendy; Keeves, John.; Mansheng, Zhou.; Power, Colin; Rajput, J. S.; Thaman, Konai Helu.; Alagumalai, Sivakumar; et al. (Dordrecht : Springer Netherlands, 2005)
This volume presents applications of the Rasch method to the real world measurement problems encountered by graduate students and other researchers. It includes an introductory section written by leaders and pioneers in the field in which the theory of the model is outlined succinctly. The major part of the book is devoted to research problems that have been addressed by a variety of applications of the Rasch measurement model using commonly available Rasch analysis programs. These examples will provide models and guidance for both researchers and students who are learning to apply the Rasch method. Each chapter outlines the research problem, describes the data used in the analysis, and presents the results of the analyses along with their interpretation. Data sets, command files and output files are available from a website for students and researchers who wish to work through any example in detail. The volume concludes with an exploration of some important extensions of the model to more complex research problems and data structures. Information about the common Rasch analysis programs is presented by their developers along with URLs for locations from which trial/demo/student versions of these programs can be downloaded.
Measurement and the Rasch model -- Classical Test Theory -- Objective Measurement -- The Rasch Model Explained -- Applications of the Rasch Model - Tests and Competencies -- Monitoring Mathematics Achievement over Time -- Manual and Automatic Estimates of Growth and Gain Across Year Levels: How Close is Close? -- Japanese Language Learning and the Rasch Model -- Chinese Language Learning and the Rasch Model -- Employing the Rasch Model to Detect Biased Items -- Raters and Examinations -- Comparing Classical and Contemporary Analyses and Rasch Measurement -- Combining Rasch Scaling and Multi-Level Analysis -- Applications of the Rasch Model - Attitudes Scales and Views -- Rasch and Attitude Scales: Explanatory Style -- Science Teachers' Views on Science, Technology and Society Issues -- Estimating the Complexity of Workplace Rehabilitation Tasks Using Rasch Analysis -- Creating a Scale as a General Measure of Satisfaction for Information and Communication Technology Users -- Extensions of the Rasch model -- Multidimensional Item Responses: Multimethod-Multitrait Perspectives -- Information Functions for the General Dichotomous Unfolding Model -- Past, Present and Future: An Idiosyncratic View of Rasch Measurement -- Epilogue -- Our Experiences and Conclusion.
Keywords: EDUCATION; DISTRIBUTION (PROBABILITY THEORY).; COMPARATIVE EDUCATION; EDUCATION; EDUCATION (GENERAL).; COMPARATIVE EDUCATION; PROBABILITY THEORY AND STOCHASTIC PROCESSES